Organic electroluminescent material of benzofluorene compound, preparation method and device

By adopting phenyl -based compounds as an unobstructed material to optimize its structure to improve the migration rate, it solves the problem of high -driving voltage, inefficient and short life of existing mechanical electrical luminous devices, and realizes low -drive voltage, high efficiency, high efficiency And the advantages of long life.

CN119371362AInactive Publication Date: 2025-01-28SHANGHAI XINRUNSHENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411421288.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing organic electroluminescent devices have problems with high driving voltage, low efficiency and short life, especially the insufficient mobility of hole blocking materials, resulting in poor device performance.

Method used

A new phenyl -based compound is used as an mechanical electrical light -derivative material. By introducing the nitrogen -containing rings and benzene ring structures, the optimized molecular symmetry and puppet torque are optimized to improve the migration rate of blocking materials.

Benefits of technology

The low -drive voltage, high hair luminous efficiency and long -life performance of the mechanical electrical light emitting devices are realized. By optimizing the compound structure, it effectively matches other layer of materials, reduces the driving voltage and improves the stability of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371362A_ABST
    Figure CN119371362A_ABST
Patent Text Reader

Abstract

The invention provides an organic electroluminescent material of a benzofluorene compound, a preparation method and a device. Wherein the nitrogen-containing heterocyclic ring is introduced to break the symmetry of molecules, and the benzene ring is introduced on the same side to reduce the dipole moment of the molecules. The sp3 hybrid carbon at the 9 position of the fluorene ring can maintain the spatial configuration of the compound, poor film-forming property and short device life caused by molecular stacking are avoided, and triazine and other functional groups with strong electron withdrawing ability are introduced, so that the mobility of the hole blocking material is effectively improved. When the compound protected by the invention is applied to the organic electroluminescent device, especially used as a hole blocking layer material, due to the asymmetric structure, the energy levels of HOMO and LUMO can be easily adjusted, and other layer materials can be effectively matched, so that the driving voltage of the device is reduced, the efficiency of the device is improved, and the service life of the device is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of organic light-emitting materials, and in particular to an organic electroluminescent material of a phenylfluorene compound and a preparation method thereof, and an organic electroluminescent device prepared by using the material as a hole blocking layer. Background Art

[0002] With the rapid development of information technology, people have put forward new goals and requirements for the performance of information display systems. Displays with high brightness, high resolution, wide viewing angle and low energy consumption have become research hotspots. Organic electroluminescent (OLED) display technology can meet the above needs of people. It also has other advantages such as wide operating temperature and flexible display. Therefore, it has become the new darling of the new generation of flat panel displays after CRT (cathode ray tube) displays, LCD (liquid crystal display) and PDP (plasma display) flat panel displays. Organic electroluminescent display technology is also known as a flat display technology with dreamy display characteristics.

[0003] An organic electroluminescent element is a self-luminescent element that uses the following principle: by applying an electric field, the fluorescent substance emits light by utilizing the recombination energy of holes injected from the anode and electrons injected from the cathode. It has the following structure: an anode, a cathode, and an organic material layer between the two. In order to improve the efficiency and stability of an organic electroluminescent element, the organic material layer generally includes multiple layers with different materials, such as a hole injection layer (HIL), a hole transport layer (HTL), a light-emitting layer, an electron transport layer (ETL), and an electron injection layer (EIL).

[0004] Hole blocking materials usually have suitable HOMO / LUMO values, which can reduce the driving voltage due to a smaller electron injection barrier. At the same time, they also need to have a higher electron transfer rate, a higher glass transition temperature, and thermal stability. Commonly used electron injection materials in the industry include azole derivatives, quinoline derivatives, and metal chelates, but some materials are easy to crystallize, which can easily lead to a shorter device life. Some materials cannot be effectively matched with the HOMO / LUMO of the adjacent functional layer materials due to their large energy gap, making it impossible to fully utilize energy and the injection barrier is too high, resulting in the problem of excessively high driving voltage and low efficiency in the device.

[0005] Therefore, developing a high-mobility hole blocking material so that an organic electroluminescent device prepared therefrom has the performance advantages of low driving voltage, high efficiency, and long life is a technical problem that needs to be solved urgently by those skilled in the art.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The technical problem to be solved by the invention is to provide an organic electroluminescent compound to produce an organic electroluminescent device with low driving voltage, high luminous efficiency, and / or long service life.

[0008] To achieve the above objectives, the embodiments of the present invention provide the following technical solutions:

[0009] An organic electroluminescent material, wherein the structure of the organic electroluminescent compound is the general formula I:

[0010]

[0011] Where:

[0012] Z1-Z3 are C or N, and at least two of them are N at the same time, preferably Z1-Z3 are N at the same time;

[0013] R is selected from C1-C6 alkyl, and R is further selected from methyl;

[0014] Ar1-Ar2 are the same or different from each other and are independently selected from the following groups or any combination thereof:

[0015]

[0016] The “*” indicates a connection point.

[0017] In the above technical solution, it is further preferred that the organic electroluminescent compound is any one of the following structures, but not limited thereto:

[0018]

[0019]

[0020]

[0021] The organic electroluminescent compound of the present invention can be prepared by a synthetic method known to those skilled in the art. For example, it is preferably prepared by the following reaction scheme.

[0022]

[0023] Wherein Hal is halogen. The definitions of the remaining groups are the same as above.

[0024] Under nitrogen protection, raw material A (1.0 eq) and raw material B (1.1-1.5 eq) are dissolved in toluene solution, potassium acetate (2.0-2.5 eq) and PdCl2 (dppf) (0.05-1.0 eq) are added, stirred evenly, heated to 100-110°C, and refluxed for 10-12 hours; after the reaction is completed, the temperature is slightly lowered, and diatomaceous earth is used for filtration to remove salt and catalyst. After the filtrate is cooled to room temperature, it is washed three times with water, the organic phase is retained, and then the aqueous phase is extracted with ethyl acetate; after the organic phases are combined, they are dried with anhydrous magnesium sulfate, and the solvent is removed with a rotary evaporator, and the remaining substance is purified by column chromatography using a mixed solution of dichloromethane and petroleum ether to obtain intermediate 1.

[0025] The intermediate 1 (1.0 eq) and the raw material C (1.0-1.2 eq) were put into a mixed solution of toluene, ethanol and water, and then ventilated 3 times. Potassium carbonate (2.0-2.2 eq) and tetrakis(triphenylphosphine)palladium (0.01-0.02 eq) were added under nitrogen protection, stirred evenly, heated to 80-90°C, and refluxed for 6-8 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain the intermediate 2.

[0026] Under nitrogen environment, raw material intermediate 2 (1.0eq) is dissolved in tetrahydrofuran (5.0-5.5eq), and liquid nitrogen is used to cool the solution to -70°C. Then, n-butyl lithium (1.1-1.5eq) is slowly injected thereinto, and the mixture is stirred for 40-50min. Subsequently, raw material D (1.1-1.5eq) dissolved in (5.0-6.0eq) tetrahydrofuran is slowly injected into the reaction vessel. The reactor is heated to room temperature, and the mixture is then stirred for 10-12h. After the reaction is completed, the reactant is poured into an aqueous ammonium chloride solution and the organic layer is separated, the solvent is removed, and the mixture is dried to obtain intermediate 3.

[0027] Intermediate 3 (1.0 eq) was dissolved in dry DCM, stirred at 0°C for 30-40 minutes, and then MSA (5.0-6.0 eq) was added dropwise. After the addition, the temperature was slowly raised to room temperature and the reaction was continued for 5-6 hours. After the reaction was completed, sodium bicarbonate was added to quench the reaction. Then, the obtained mixture was extracted with dichloromethane to obtain an organic phase, which was then treated with anhydrous magnesium sulfate to remove moisture, and the residue obtained was separated and purified by flash column chromatography to obtain intermediate 4.

[0028] Add intermediate 4 (1.0 eq) and t-BuOK (1.5-1.7 eq) to a reaction flask, add DMF solvent, and stir to mix thoroughly. Add CH3I (1.0-2.0 eq) dropwise at room temperature, heat to 100-120°C, react for 1 hour, then add CH3I (2.0-2.3 eq) dropwise, react for 2 hours, then add CH3I (2.0-2.3 eq) dropwise, and react overnight. Cool to room temperature, pour the reaction solution into cold water, then extract with ethyl acetate, wash twice with water, then dry with anhydrous magnesium sulfate, and finally purify the remaining substance by column chromatography using a mixture of dichloromethane and petroleum ether as eluent to obtain intermediate 5.

[0029] Under nitrogen protection, intermediate 5 (1.0 eq) and raw material E (1.1-1.3 eq) were put into a mixed solution of toluene, ethanol and water, followed by ventilating 3 times. Potassium carbonate and tetrakis(triphenylphosphine)palladium were added under nitrogen protection, stirred evenly, heated to 90°C, and refluxed for 8 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain intermediate 6.

[0030] Under nitrogen protection, raw material F-1 (1.1-1.3eq) and raw material F-2 (1.0eq) are put into a mixed solution of toluene, ethanol and water, followed by ventilating 3 times, adding potassium carbonate and tetrakis(triphenylphosphine)palladium under nitrogen protection, stirring evenly, heating to 80-90°C, reflux reaction for 6-8h, and after the reaction is completed, the temperature is slightly lowered, and diatomaceous earth is used for filtration to remove salt and catalyst. After the filtrate is cooled to room temperature, it is washed with water three times, the organic phase is retained, and the aqueous phase is extracted with ethyl acetate; after the organic phases are combined, they are dried with anhydrous magnesium sulfate, and the solvent is removed with a rotary evaporator to obtain intermediate F.

[0031] Under nitrogen protection, the intermediate F (1.0 eq) and the raw material F-3 (1.1-1.2 eq) are dissolved in a toluene solution, potassium acetate (2.0-2.2 eq) and PdCl2 (dppf) (0.05-1.0 eq) are added, stirred evenly, heated to 90-100 ° C, and refluxed for 10-12 hours; after the reaction is completed, the temperature is slightly lowered, and diatomaceous earth is used for filtration to remove salt and catalyst. After the filtrate is cooled to room temperature, it is washed three times with water, the organic phase is retained, and then the aqueous phase is extracted with ethyl acetate; after the organic phases are combined, they are dried with anhydrous magnesium sulfate, and the solvent is removed with a rotary evaporator. The remaining substance is purified by column chromatography using a mixed solution of dichloromethane and petroleum ether to obtain raw material F.

[0032] Under nitrogen protection, the intermediate 6 (1.0 eq) and the raw material F (1.1-1.3 eq) were stirred evenly in a mixed solvent of toluene, ethanol and water (volume ratio of 2:1:1), and X-Phos (0.05-1.0 eq), palladium acetate (Pd(OAc)2) (0.05-1.0 eq), and cesium carbonate (2.0-2.2 eq) were added. After sufficient stirring, the temperature was raised to 80-90°C and stirred for reaction for 8-10 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain the compound shown in the general formula 1.

[0033] wherein R, Ar1-Ar3, Z1-Z3 are as defined above, and Hal1-Hal5 are selected from fluorine, chlorine, bromine and iodine, respectively.

[0034] The present invention also provides an organic electroluminescent device, wherein the organic layer comprises the organic electroluminescent material of the present invention. Preferably, the material of the present invention is used as an organic hole blocking material EBL.

[0035] The present invention also provides a panel, which uses the organic electroluminescent device of the present invention.

[0036] The beneficial effects of the present invention are:

[0037] The invention provides an organic hole blocking material. The organic electroluminescent device prepared by using the compound has the performance advantages of low driving voltage, high efficiency and long life.

[0038] The introduction of a nitrogen-containing heterocyclic ring breaks the symmetry of the molecule, and the introduction of a benzene ring on the same side reduces the dipole moment of the molecule. 3 Hybridized carbon can maintain the spatial configuration of the compound, avoid molecular stacking that leads to poor film-forming properties and short device life, and introduce functional groups with strong electron-withdrawing ability such as triazine to effectively improve the mobility of the hole blocking material. When the compound protected by the present invention is used in an organic electroluminescent device, due to its asymmetric structure, it is easy to adjust the energy levels of HOMO and LUMO, and can effectively match other layer materials, thereby reducing the driving voltage of the device, improving the efficiency of the device, and extending the device life. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is the hydrogen nuclear magnetic resonance spectrum of compound 2 in Example 1. DETAILED DESCRIPTION

[0040] Example 1

[0041]

[0042]

[0043] Under nitrogen protection, raw material A (1.0 eq) (CAS: 31928-44-6) and raw material B (1.1 eq) (CAS: 73183-34-3) were dissolved in a toluene solution, potassium acetate (2.0 eq) and PdCl2 (dppf) (0.05 eq) were added, stirred evenly, heated to 100°C, and refluxed for 12 hours; after the reaction was completed, the temperature was slightly lowered, diatomaceous earth was used for filtration to remove salt and catalyst, and the filtrate was cooled to room temperature and washed three times with water, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator, and the remaining substance was purified by column chromatography using a mixed solution of dichloromethane and petroleum ether (v:v=1:6) to obtain intermediate 1. (Yield, 85.7%)

[0044] The intermediate 1 (1.0 eq) and the raw material C (1.0 eq) (CAS: 615-42-9) were put into a mixed solution of toluene, ethanol and water, and then ventilated 3 times. Potassium carbonate (2.0 eq) and tetrakis(triphenylphosphine)palladium (0.01 eq) were added under nitrogen protection, stirred evenly, heated to 90°C, and refluxed for 8 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, and the organic phase was retained. Then, the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain the intermediate 2. (Yield, 80.4%)

[0045] Under nitrogen environment, the raw material intermediate 2 (1.0 eq) was dissolved in tetrahydrofuran (5.0 eq), and the solution was cooled to -70 ° C using liquid nitrogen. Then, n-butyl lithium (1.1 eq) was slowly injected thereinto, and the mixture was stirred for 40 min. Subsequently, the raw material D (1.1 eq) (CAS: 100-52-7) dissolved in (5.0 eq) tetrahydrofuran was slowly injected into the reaction vessel. The reactor was heated to room temperature, and the mixture was then stirred for 12 h. After the reaction was completed, the reactant was poured into an aqueous ammonium chloride solution and the organic layer was separated, the solvent was removed, and the intermediate 3 was obtained. (Yield: 75.6%)

[0046] Intermediate 3 (1.0 eq) was dissolved in dry DCM, stirred at 0°C for 30 minutes, and then MSA (5.0 eq) was added dropwise. After the addition, the temperature was slowly raised to room temperature and the reaction was continued for 5 hours. After the reaction was completed, sodium bicarbonate was added to quench the reaction. Then, the obtained mixture was extracted with dichloromethane to obtain an organic phase, which was then treated with anhydrous magnesium sulfate to remove moisture, and the residue thus obtained was separated and purified by flash column chromatography to obtain Intermediate 4. (Yield: 72.4%)

[0047] Add intermediate 4 (1.0 eq) and t-BuOK (1.5 eq) to a reaction flask, add DMF solvent, and stir to mix thoroughly. Add CH3I (1.0 eq) dropwise at room temperature, heat to 100°C, react for 1 hour, then add CH3I (2.0 eq) dropwise, react for 2 hours, then add CH3I (2.0 eq) dropwise, and react overnight. Cool to room temperature, pour the reaction solution into cold water, then extract with ethyl acetate, wash twice with water, then dry with anhydrous magnesium sulfate, and finally use a mixture of dichloromethane and petroleum ether as eluent (V DCM :V PE =1:14), and the remaining material was purified by column chromatography to obtain intermediate 5. (Yield: 59.8%)

[0048] Under nitrogen protection, intermediate 5 (1.0 eq) and raw material E (1.1 eq) (CAS: 98-80-6) were put into a mixed solution of toluene, ethanol and water, and then ventilated 3 times. Potassium carbonate and tetrakis(triphenylphosphine)palladium were added under nitrogen protection, stirred evenly, heated to 90°C, and refluxed for 8 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain intermediate 6. (Yield, 82.8%)

[0049] Under nitrogen protection, raw material F-1 (1.1 eq) (CAS: 98-80-6) and raw material F-2 (1.0 eq) (CAS: 1613576-54-7) were put into a mixed solution of toluene, ethanol and water, and then ventilated 3 times. Potassium carbonate and tetrakis(triphenylphosphine)palladium were added under nitrogen protection, stirred evenly, heated to 90°C, and refluxed for 8 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain intermediate F. (yield, 77.9%)

[0050] Under nitrogen protection, the intermediate F (1.0 eq) and the raw material F-3 (1.1 eq) (CAS: 73183-34-3) were dissolved in a toluene solution, potassium acetate (2.0 eq) and PdCl2 (dppf) (0.05 eq) were added, stirred evenly, heated to 100°C, and refluxed for 12 hours; after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator, and the remaining substance was purified by column chromatography using a mixed solution of dichloromethane and petroleum ether (v:v=1:8) to obtain raw material F. (yield, 71.9%)

[0051] Under nitrogen protection, intermediate 6 (1.0 eq) and raw material F (1.1 eq) were stirred evenly in a mixed solvent of 280 mL toluene, ethanol and water (volume ratio of 2:1:1), and X-Phos (0.05 eq), palladium acetate (Pd(OAc)2) (0.05 eq), and cesium carbonate (2.0 eq) were added. After sufficient stirring, the temperature was raised to 90°C and stirred for reaction for 10 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain compound 2. The yield of compound 2 was calculated to be 66.6%.

[0052] MS (ESI, m / Z): [M+H]+: 715.57

[0053] Elemental Analysis:

[0054] Calculated values: C, 88.92; H, 5.21; N, 5.87.

[0055] The test values ​​are: C, 88.07; H, 5.47; N, 6.15.

[0056] Example 2

[0057]

[0058]

[0059] The synthesis method of intermediate 6 is consistent with that in Example 1.

[0060] Under nitrogen protection, raw material F-1 (1.1 eq) (CAS: 98-80-6) and raw material F-2 (1.0 eq) (CAS: 1613576-54-7) were put into a mixed solution of toluene, ethanol and water, and then ventilated 3 times. Potassium carbonate and tetrakis(triphenylphosphine)palladium were added under nitrogen protection, stirred evenly, heated to 90°C, and refluxed for 8 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain intermediate F. (yield, 80.2%)

[0061] Under nitrogen protection, the intermediate F (1.0 eq) and the raw material F-3 (1.1 eq) (CAS: 73183-34-3) were dissolved in a toluene solution, potassium acetate (2.0 eq) and PdCl2 (dppf) (0.05 eq) were added, stirred evenly, heated to 100°C, and refluxed for 12 hours; after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator, and the remaining substance was purified by column chromatography using a mixed solution of dichloromethane and petroleum ether (v:v=1:8) to obtain raw material F. (yield, 73.1%)

[0062] Under nitrogen protection, intermediate 6 (1.0 eq) and raw material F (1.1 eq) were stirred evenly in a mixed solvent of 280 mL toluene, ethanol and water (volume ratio of 2:1:1), and X-Phos (0.05 eq), palladium acetate (Pd(OAc)2) (0.05 eq), and cesium carbonate (2.0 eq) were added. After sufficient stirring, the temperature was raised to 90°C and stirred for 10 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain compound 2. The yield of compound 2 was calculated to be 58.4%.

[0063] MS (ESI, m / Z): [M+H]+: 715.58

[0064] Elemental Analysis:

[0065] Calculated values: C, 88.92H, 5.21; N, 5.87.

[0066] The test values ​​are: C, 88.14; H, 5.54; N, 6.13.

[0067] The synthesis methods of other compounds are the same as those in the above examples, which are not described one by one here. The mass spectrometry test is performed using a Waters XEVO TQD mass spectrometer, which has low precision, and is tested using an ESI source. The mass spectrometry test values, molecular formulas, and yields of other synthesis examples are shown in Table 1 below:

[0068] Table 1 Synthesis results test:

[0069]

[0070]

[0071] Device application example 1: Preparation of organic electroluminescent devices

[0072] a. I TO anode: Wash the I TO (indium tin oxide)-Ag-I TO (indium tin oxide) glass substrate with a coating thickness of 150nm in distilled water twice, ultrasonically wash for 30 minutes, and then repeatedly wash it with distilled water twice, ultrasonically wash for 10 minutes. After washing, transfer it to a spin dryer for drying, and finally bake it in a vacuum oven at 220℃ for 2 hours. After baking, cool it down and it can be used. Use this substrate as the anode, use an evaporation machine to carry out the evaporation device process, and evaporate other functional layers on it in sequence.

[0073] b. HIL (hole injection layer): The hole injection layer materials HT-1 and P-dopant are vacuum evaporated at a deposition rate of 97:3, and the thickness is 10 nm;

[0074] c. HTL (hole transport layer): The evaporation rate is 130nm, and HT-1 is vacuum evaporated on the hole injection layer as a hole transport layer. The structure is shown below;

[0075] d. Light-emitting auxiliary layer: At a deposition rate of 10 nm, EB-1 was vacuum-deposited on the hole transport layer as a light-emitting auxiliary layer.

[0076] e. EML (light-emitting layer): Then on the above-mentioned light-emitting auxiliary layer, The host material (Host) and dopant material (Dopant) with a thickness of 20nm are vacuum-deposited as the light-emitting layer. The chemical formulas of Host and Dopant are shown below. The evaporation rate ratio of Host to Dopant is 98:2.

[0077] f. HBL (hole blocking layer): At a deposition rate of , 5 nm of the compound 2 provided in the above embodiment is vacuum-deposited on the light-emitting layer as a hole blocking layer;

[0078] g. ETL (Electron Transport Layer): At a deposition rate of , 30 nm of ET-1 was vacuum evaporated on the hole blocking layer as an electron transport layer.

[0079] h. EIL (electron injection layer): At a evaporation rate of , a 1.0 nm Yb film layer was evaporated to form an electron injection layer.

[0080] i. Cathode: The evaporation rate ratio is 1:9, and magnesium and silver are evaporated at 18nm, and the evaporation rate ratio is 1:9 to obtain an OLED device.

[0081] j. Light extraction layer: The evaporation rate is 70nm, and CPL-1 with a thickness of 70nm is vacuum evaporated on the cathode as a light extraction layer. The evaporated substrate is then packaged. First, the cleaned cover is coated with UV glue using a glue coating device, and then the coated cover is moved to the pressing section, and the evaporated substrate is placed on the upper end of the cover. Finally, the substrate and the cover are bonded by the bonding equipment, and the UV glue is cured by light.

[0082] The structural formula of the materials used is shown below:

[0083]

[0084] Device Application Example 2 to Device Application Example 16 Referring to the above method, the compound 2 used in Device Application Example 11 is replaced by compound 18, compound 3, compound 5, compound 7, compound 12, compound 14, compound 15, compound 17, compound 20, compound 22, compound 27, compound 33, compound 39, compound 40, and compound 43 as hole blocking layers to prepare corresponding organic electroluminescent devices.

[0085] Device Comparative Example: This comparative example provides an organic electroluminescent device. The only difference between the preparation method of the organic electroluminescent device and the device embodiment 1 is that the organic electroluminescent device uses existing comparative compounds a, b, and c to replace the hole blocking layer (compound 2) in the above device embodiment 1 for evaporation to prepare device comparative examples 1-3. Among them, the chemical structural formulas of comparative compounds a, b, and c are:

[0086]

[0087] The driving voltage, luminous efficiency and life of the organic electroluminescent devices obtained from the device embodiments 2-16 and the device comparative examples 1-3 were characterized at a brightness of 1000 (ns). The test results are shown in Table 2 below:

[0088] Table 2 Device performance

[0089]

[0090]

[0091] Note: In blue top-emitting devices, the current efficiency is greatly affected by chromaticity. Therefore, the influence of chromaticity on efficiency is taken into account, and the ratio of luminous efficiency to CIEy is defined as BI value, that is, BI = (cd / A) / CIEy.

[0092] As shown in Table 2, the organic electroluminescent device prepared by using the organic electroluminescent compound provided by the present invention as a hole blocking layer has a lower starting voltage, and the luminous efficiency and life are significantly improved compared with the organic electroluminescent device prepared by using compounds a, b, and c as a hole blocking layer. Specifically, compared with the comparative example compound b, compound 2 introduces a phenyl group at the ortho position of triazine to increase the molecular conjugation, avoid the aggregation effect between molecules, and has the characteristics of being difficult to crystallize, difficult to aggregate, and having good film-forming properties between molecules. Compared with the comparative example compound c, compound c is a triazine group and a phenyl group and a parent nucleus that is substituted at 1, 3, 5 positions, and the steric hindrance is greater, and the left side of the parent nucleus of compound c is connected to an aromatic group, and the dipole moment is larger than that of compound 2, so the organic electroluminescent device prepared by using the compound of the present invention has the performance advantages of low driving voltage, high efficiency, and long life.

[0093] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. An organic electroluminescent material of a phenylfluorene compound, wherein the structure of the organic electroluminescent compound is the general formula I: Where: Z1-Z3 are C or N, and at least 2 of them are N at the same time; R is selected from C1-C6 alkyl; Ar1-Ar2 are the same or different from each other and are independently selected from the following groups or any combination thereof: The "*" indicates a connection point.

2. The organic electroluminescent material according to claim 1, characterized in that: Z1-Z3 are N at the same time.

3. The organic electroluminescent material according to claim 1, characterized in that: R is selected from methyl.

4. The organic electroluminescent material according to claim 1, characterized in that: The organic electroluminescent compound is any one of the following structures:

5. The method for preparing an organic electroluminescent material according to any one of claims 1 to 4, characterized in that The following reaction scheme is used to prepare: Wherein Hal is a halogen.

6. An organic electroluminescent device, wherein the organic layer comprises the organic electroluminescent material according to any one of claims 1 to 4.

7. The organic electroluminescent device according to claim 6, characterized in that: The organic electroluminescent material according to any one of claims 1 to 4 is used as a hole blocking layer of a device.

8. A panel, characterized in that: The organic electroluminescent device according to any one of claims 6 to 7 is used.